Frequency of IDH1 mutation in adult-type diffuse astrocytic gliomas in a tertiary hospital in Kenya - Gakinya, Samuel; Mutuiri, Anderson; Onyuma, Timothy; Cheserem, Beverly; Mogere, Edwin (Frontiers in Medicine, 2024)
The 2021 WHO classification of gliomas has separated gliomas based on their IDH mutation status, reflecting differences in their pathogenesis and clinical characteristics. There is a paucity of data on the prevalence of IDH mutations in gliomas in this region. This study aimed to determine the frequency of the IDH1 mutation in adult-type diffuse astrocytic gliomas in a tertiary hospital in Kenya. Approximately half of the gliomas were positive for the IDH1 mutation, with a slight male predominance. Our study provides crucial insights into the frequency of IDH1 mutations in gliomas in Kenya.